Cognitive outcome of aneurysmal subarachnoid haemorrhage after clipping or coiling : a comparative post intervention study in a hospital population - Pantelis, Eleni (Department of Psychology, 2014)
Subarachnoid haemorrhage secondary to ruptured cerebral aneurysm and clipping are associated with substantial morbidity and mortality. Despite favourable neurological outcomes, many patients report persistent cognitive and emotional deficits post intervention. To compare cognitive and quality of life outcomes in patients with ruptured aneurysmal subarachnoid haemorrhage treated with surgical clipping or endovascular coiling. Twenty-four patients with aneurysmal subarachnoid haemorrhage treated by clipping or coiling were retrospectively assessed by use of a battery of cognitive tests and a quality of life questionnaire. All patients had favourable grades on admission, that is, WFNS <= 2 and favourable neurological grades on discharge, that is, GOS <=2. treated with surgical clipping or endovascular coiling. Patients in the two treatment groups were matched on age, years of education and on premorbid IQ. The two groups were further matched on time from intervention to assessment and number of treatments. The cognitive performance of the treatment groups was compared to hospitalised controls, matched for age, years of education and premorbid IQ. Comparison of cognitive outcome between the two groups indicated a trend towards poorer outcome in the surgical group which achieved significance on six test measures. There were no significant differences with respect to the quality of life measure. Patients surviving aneurysmal subarachnoid haemorrhage are likely to suffer from a 'subarachnoid-induced encephalopathy' which appears to be more aggravated by the invasive nature of surgery, compared to endovascular coiling, as demonstrated by the poorer cognitive performance ofthe clipping patients.